Eva Wiklund; Pre-slaughter handling of reindeer (Rangifer tarandus tarandus L.) - effects on meat quality - REH, Ed. (Rangifer, 1997)
Eva Wiklund defended her PhD-thesis in Agriculture "Pre-slaughter handling of reindeer (Rangifer tarandus tarandus L.) - effects on meat quality" at the Swedish University of Agricultural Sciences (SLU), Uppsala, Sweden, on December 20, 1996.